Innovate to Liberate: Akselerasi Kreativitas Siswa dalam Pendidikan - Crisvin; Masduki Asbari; Jacelyn Valencia Chiam (Journal of Information Systems and Management (JISMA), 2023)
The aim of this study is to identify the role of the teacher's paradigm in enhancing student creativity within the "Merdeka Belajar" (Freedom to Learn) program. The research report utilizes a qualitative descriptive methodology through participant observation, as data was obtained by listening to the spoken narrative on the YouTube channel of the Ministry of Education and Culture of the Republic of Indonesia, titled "Simultaneously Innovate, Realize Freedom to Learn," presented by Minister Nadiem Makarim. The research findings demonstrate that the teacher's paradigm, acting as a facilitator and driving force in implementing the "Merdeka Belajar" program, significantly positively impacts student creativity. The "Merdeka Belajar" program effectively supports innovative learning through Android-based applications accessible without internet data restrictions and underscores the importance of a humanistic approach and differentiated learning to create an educational ecosystem that nurtures student creativity. This research initiative stems from the Indonesian government's efforts, particularly the Ministry of Education, to enhance educational quality through the "Merdeka Belajar" program. Spearheaded by Minister Nadiem Makarim, this program aims to provide students with learning freedom, reduce overly dense curricula, and encourage creativity and innovation in the learning process.